Complicated Long Term Vaccine Induced Thrombotic Immune Thrombocytopenia—A Case Report - Albrecht Günther (MDPI AG, 2021)
Background and Objectives: Vaccine induced thrombotic thrombocytopenia (VITT) may occur after COVID-19 vaccination with recombinant adenoviral vector-based vaccines. VITT can present as cerebral sinus and venous thrombosis (CSVT), often complicated by intracranial hemorrhage. Today it is unclear, how long symptomatic VITT can persist. Here, we report the complicated long-term course of a VITT patient with extremely high titers of pathogenic anti-platelet factor 4 (PF4)-IgG antibodies. Methods: Clinical and laboratory findings are presented, including the course of platelet counts, D-Dimer levels, clinical presentation, imaging, SARS-CoV-2-serological and immunological, platelet activating anti-PF4-IgG, as well as autopsy findings. Results: The patient presented with extended superior sagittal sinus thrombosis with accompanying bifrontal intracerebral hemorrhage. Repeated treatment with intravenous immune globuline (IVIG) resolved recurrent episodes of thrombocytopenia. Moreover, the patient’s serum remained strongly positive for platelet-activating anti-PF4-IgG over three months. After a period of clinical stabilization, the patient suffered a recurrent and fatal intracranial hemorrhage. Conclusions: Complicated VITT with extremely high anti-PF4-IgG titers over three months can induce recurrent thrombocytopenia despite treatment with IVIG and anticoagulation. Plasma exchange, immunoadsorption, and /or immunosuppressive treatment may be considered in complicated VITT to reduce extraordinarily high levels of anti-PF4-IgG. Long-term therapy in such cases must take the individual bleeding risk and CSVT risk into account.